Hierarquias e poderes no cotidiano escolar: da organização burocrática à organização de pessoas - Santos, Silmar Leila dos (2011)
This work considered as an object of study the existing social relations as an expression of hierarchy and power relations between agents of a fundamental education school in municipality of São Paulo. Discusses the reality school regarding the need for understanding of their organization in various areas focusing on the possibilities of existence hierarchies and powers parallels generated in diverse dynamic, but always coming from social interactions. The general objective was to clarify the questions of hierarchies and powers diversified expressed by those who live from day to day school, having the following objectives: characterize the organization of everyday school, considering the hierarchy provided and the possible manifestations of different hierarchies and powers of their various agents; register potential conflicts between teachers and other agents that circulate in school and identify which agents possessed some kind of leadership by obtaining configurations and their dynamics. The research was developed between December 2008 and December 2009 involving teachers, school administrative agents, management team and other agents found in school, beyond the daily observation in the field, opted for the application of a questionnaire, to obtain of some of the characteristics of the group of school teachers surveyed and, the application of the sociometric test, developed by Moreno (1962) as a instrument study of social structures, able to provide a graphical representation of the formation of groups and also the highlights of choice and rejection on various of criteria. The information were analyzed based on concepts de Max Weber, Licínio Lima, Norbert Elias e Randal Collins. The results showed the existence of a plurality in the characteristics of school organization, with the living together of models guided by formal rules, informals and non formal; the existence of hierarchies and powers parallels that come, daily, by means of dynamic of relational webs of interdependencies in situations that establish different configurations by means of chains of interaction ritual, feelings of belonging and episodes of solidarity and conflict as faces of the same coin